PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA KEPERAWATAN - asnah asnah; Rus Andraini; Rahmawati Shoufiah (MNJ (Mahakam Nursing Journal), 2017)
This study aims to know the (1) an overview assessment of the quality of student services, (2) the influence of service quality dimensions include tangibles, reliability, responsiveness, assurance and empathy to the satisfaction of students, (3) the influence of student satisfaction to student loyalty. The research was carried out inProdi D-III Nursing Class Balikpapan Poltekkes Kemenkes Kaltim. The method used in this study is correlational survey. Sampling was done randomly from the three departements in Prodi D-III Nursing Class Balikpapan Poltekkes Kemenkes Kaltim. Data ware analyzed uusing statistical analysis, descriptive analysis using the importance performance analysis. This analysis is followed by the mapping into the Cartesian diagram to see the position oof each quality attribute, folloowed by regression analysis. The results of this study indicate student asessment of quality of service in Prodi D-III Nursing Class Balikpapan Poltekkes Kemenkes Kaltim still perceived to be belaow expectations because there is a gap for student 19,30%, Service quality has a positive effect on student satisfaction of D-III Nursing Program of Balikpapan Poltekkes Kemenkes Kaltim. Keyword: Quality Service and Satisfaction